Clinical evaluation of a novel head protection system for interventional radiologists. Issue 147 (February 2022) - Bärenfänger, Felix; Walbersloh, Jörg; El Mouden, Rachid; Goerg, Fabian; Block, Andreas; Rohde, Stefan
Abstract: Purpose: A novel two-part protective system consisting of a modified thyroid collar and a head protection is intended to reduce the radiation dose to the examiners head during fluoroscopy-guided interventions. In this pilot study, we tested this protection system under real-life conditions in general radiological and neuroradiological interventions. Methods: Two sets of the protection system (set A and B) were equipped with 12 thermoluminiscence detectors (TLD). For simultaneous measurement of radiation exposure and dose-reduction, each six TLDs were fixed to the inner side and on the corresponding outer side of the protection system. Set A was used exclusively for general radiological interventions and set B exclusively for neuroradiological interventions. To compare the staff exposure in general radiology and neuroradiology, dose values were normalized to a DAP of 10 000 µGy∙m 2 . Results: The sets were tested during 20 general radiological interventions and 32 neuroradiological interventions. In neuroradiology, the mean normalized radiation exposure was 13.44 ± 1.36 µSv/10 000 µGy∙m 2 at the head protection and 22.27 ± 2.09 µSv/10 000 µGy∙m 2 at the thyroid collar. In general radiology, the corresponding results were 29.91 ± 4.19 µSv/10 000 µGy∙m 2 (head protection) and 68.07 ± 17.25 µSv/10 000 µGy∙m 2 (thyroid collar). Thus, mean dose exposure was 2.5 times higher in general radiological interventions (p = 0.016). The use of the protection system resulted in a mean dose reduction of 81.2 ± 11.1 % (general radiology) and 92.1 ± 4.2 % (neuroradiology; p = 0.016). Conclusion: Fluoroscopy-guided interventions lead to significant radiation exposure of the head area for the examiner. The novel protection system tested led to a significant dose reduction of 80–90%, depending on the type of intervention.